Inflammatory Bowel Disease (IBD)—A Textbook Case for Multi-Centric Banking of Human Biological Materials - Cleynen, Isabelle; Linsen, Loes; Verstockt, Sare; Verstockt, Bram; Ballet, Vera; Vandeput, Eline; Van Assche, Gert; Ferrante, Marc; Van Landuyt, Kristel; Vermeire, Séverine; Ectors, Nadine (Frontiers in Medicine, 2019)
Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory condition affecting mainly the gastro-intestinal tract with two main entities: Crohn’s disease (CD) and ulcerative colitis (UC). Although the exact mechanisms underlying the initial development of inflammatory bowel disease are not fully understood, it is believed that an abnormal immune response is elicited against the intestinal microbiota in genetically predisposed individuals. Crucial elements of the etiopathogenesis have been elucidated by research using human biological materials. The estimated prevalence of IBD is 0.5% in the Western world. Although incidence rates are increasing, both conditions are not “common” in general terms mandating a multicentric approach. Biological material from numerous Belgian patients have been collected over time in a number of university hospitals in Belgium (UH Ghent : 800 CD patients, 350 UC patients, 600 normal controls ; UH Leuven : 2600 CD patients, 1380 UC patients, 98 IC/IBDU patients, 6260 normal controls). Within the setting of the Flemish Centre Medical Innovation initiative and later on the Flemish biobank network a prospective study was set-up across three Belgian IBD centers (University Hospitals Brussels, Ghent and Leuven). Human biological materials and data have been collected prospectively from newly diagnosed CD and UC patients. The analyses hereof have generated new insights which have been published in the most renowned journals. The approach of well-thought off, multi-centric, structured and systematic biobanking has proven to be a success-story and thus a textbook case for multi-centric banking of human biological materials. This story is being told in this article.